Pickering Emulsion-Based Microreactors for Size-Selective Interfacial Enzymatic Catalysis - Lei, Jieqing; Qi, Liang; Luo, Zhigang (Frontiers in Bioengineering and Biotechnology, 2020)
In this study, we have developed a mild and effective method to prepare a metal-organic framework (MOF)-based microcapsule by the self-assembly of pre-synthesized zeolite imidazolate framework-8 (ZIF-8) nanoparticles at the oil-water interface combined with deposition of a dense ZIF-8 coating outside the capsule. By introducing the enzyme Candida antarctica lipase B (CalB) directly into the stabilizer ZIF-8 or the water phase of Pickering emulsion during the preparation process, we achieved that the enzyme was immobilized within the shell (CalB@ZIF-8@cap) or in the cavity (ZIF-8@cap-CalB) of the microcapsules, respectively. The resulting CalB-loaded microcapsules were robust and had a core-shell structure proved by scanning electron microscopy. Meanwhile, Fourier transform infrared spectroscopy was conducted to confirm the encapsulation of enzymes in the microcapsules and their position in the microcapsules was confirmed by fluorescence microscopy. Furthermore, through the comparison of transesterification reactions between a pair of small substrates and a pair of larger ones, the two types of CalB-loaded microcapsules showed great catalytic activity, stability and size selectivity, and the catalytic activity of CalB@ZIF-8@cap was slightly higher than that of ZIF-8@cap-CalB. Importantly, due to the large size of the microcapsules, the catalyst could be separated from the reaction system by sedimentation, thereby reducing the energy consumption for separation. These kinds of multifunctional MOF-enzyme composites may open up new opportunities for the biocatalysis and microreactor.